Protein-losing enteropathy in camptodactyly-arthropathy-coxa vara-pericarditis (CACP) syndrome. Issue 1 (December 2016) - Peters, Bram; Schuurs-Hoeijmakers, Janneke; Fuijkschot, Joris; Reimer, Annette; van der Flier, Michiel; Lugtenberg, Dorien; Hoppenreijs, Esther
Abstract Background Camptodactyly-arthropathy-coxa vara-pericarditis (CACP, OMIM: #208250) syndrome is a rare autosomal recessive disease that can be difficult to recognise not only because of its wide clinical variability but also because of its clinical resemblance to juvenile idiopathic arthritis (JIA). PRG4 is the only gene so far known to be associated with CACP syndrome. Children with CACP syndrome lack the glycoprotein lubricin due to recessive mutations in PRG4. Lubricin serves as a lubricant in joints, tendons and visceral cavities (pleural cavity, pericardium) and inhibits synovial proliferation. Children with CACP syndrome suffer from congenital camptodactyly, arthropathy, coxa vara and sometimes pericarditis. This report concerns a child with CACP syndrome complicated by protein-losing enteropathy (PLE), caused by constrictive pericarditis and so contributes to knowledge of the presentation of CACP syndrome. Case Presentation A 10- year-old girl with consanguineous parents suffered from congenital camptodactyly and progressive swollen and painful joints. Her father and his sister had similar childhood-onset joint complaints. Laboratory tests showed no signs of inflammation but showed persistent low protein- and IgG- levels, indicating a secondary immunodeficiency. Increased alpha antitrypsin clearance confirmed PLE. Abdominal ultrasound with Doppler showed hepatomegaly and portal hypertension. Echocardiography suggested constrictive pericarditis. However, heart catheterization could not confirm this. Ultrasound and X-ray examination of the joints combined with a puncture of the synovial fluid were performed. These results, combined with the clinical presentation and the consanguinity, suggested CACP syndrome. Due to excessive enteral protein losses, the patient was treated with Cotrimoxazol prophylaxis and immunoglobulin supplements. These supplements were inadequate to achieve normal IgG values. As constrictive pericarditis with subsequent PLE was the best explanation for the excessive IgG losses, pericardiectomy was performed with good results. Genetic testing in our patient was complicated but revealed a pathogenic mutation within the repeat sequence in exon 7 of the PRG4 gene. Conclusion PLE resulting from constrictive pericarditis can be a complication of CACP syndrome. As serious complications can arise from the resulting secondary immunodeficiency, we recommend regular evaluation of clinical symptoms of constrictive pericarditis and PLE in children with CACP syndrome.